A pack for autumn - Emerson, Emilia (Cozyverse, 2024)
"Starlight Grove needs a new Lighthouse Keeper and Olive Autumn Harvest needs a fresh start. Preferably one with as much solitude as possible. So, her new job and isolated ocean cottage is perfect-except for the eccentric, meddling townspeople, and the cat who's adopted her. When the town wins a grant for lighthouse restoration, Olive is forced to let the contractors into her space...a company comprised of three hot alphas: Easton, her golden retriever stalker. Lars, the steady, protective viking. And Finn, who's hiding a pain that matches her own. Suddenly, these guys are everywhere-and they're completely unfazed by Olive's prickly personality as they try to care for her, protect her, and court her. But everyone in this relationship is holding on to secrets... and it might not just be the lighthouse that needs restoration."--Amazon.